Pengembangan Media Pembelajaran Kartu Cerdas sebagai Penguatan Keterampilan Membaca Siswa Kelas Rendah di Sekolah Dasar - I'in Mur Arizah; Yunika Afryaningsih; Dessy Setyowati (Edu Berkah Khatulistiwa, 2023)
This researcher aims to develop Smart Card learning media which is motivated by the lack of utilization of the media used by educators until causing monotony and lack of student response in learning so that it has an impact on reading skills. The use of media in learning can help foster student focus. Smart Cards are cards that contain writing and pictures, so students can easily digest the writing with the help of pictures. This research is a development research that refers to the developer model Borg and Gallaccording to the developer which uses seven stages in the research namely Research and Information Collection, Planning, Develop Preliminary Form of Product, Preliminary Field Testing, Operational Product Revision, Main Field Testing, Operational Field Testing. Based on the research results, validation results of media experts obtained score data of 92% with the criteria of